ANALISA DAN STRATEGI PENGEMBANGAN WISATA HUTAN PINUS NONGKO IJO DI KABUPATEN MADIUN - yoga adi pratama (Pemerintah Kabupaten Madiun, 2022)
The Madiun Regency Government through the Youth and Sports Tourism Office is very serious about developing tourism potential around the Wilis. One of the potential tourist objects that can be an alternative is the Nongko Ijo pine forest. The Nongko Ijo Pine Forest is a natural tourist destination located on the western slopes of Mount Wilis, to be precise in Kare Village, Kare District, Madiun Regency, East Java.Therefore, a deeper study of analysis and development strategies for each tour needs to be carried out to serve as a guide, direction, and reference for the Tourism Office and Madiun Regency government stakeholders to carry out the arrangement and development of Nongko Ijo Pine Forest tourism. The study process was carried out using the descriptive analysis method, the SWOT analysis method, and the EFAS and IFAS analysis methods. Based on the results of the analysis carried out, it can be concluded that the Nongko Ijo pine forest tourism development plan is to collaborate with the Kandangan Coffee plantation, Kare District. This priority area is divided into five tourism activity zones, namely: 1) the information and service center zone, 2) the coffee village zone, 3) the coffee education tourism zone, 4) the forest ecotourism zone, and 5) the homestay zone. Keywords: SWOT, EFAS dan IFAS, Nongko Ijo